THE VISUALIZATION METACOGNITIVE STRATEGY TO IMPROVE READING COMPREHENSION - Putri Restu Damayanti; Siti Sarah Fitriani; Saiful Marhaban (English Education Journal, 2020)
Improving the reading comprehension of the students requires creativity in finding the strategy and motivation to read. Therefore, this research aims to implement visualization metacognitive strategy to improve the students’ reading comprehension. The researcher focuses on the implementation of visualization metacognitive strategy in improving the reading comprehension by using recount text. Then she also limits the scope on reading sub-skills that consists of main idea, supporting details, inference, reference, and vocabulary.  This research used tests which are divided to pretest and post-test and also questionnaire as the instruments. The samples were the students from SMAN 4 Banda Aceh, which consisted of 66 students and divided into experimental class and control class. The scores were tabulated statistically by using t-test. Then, the researcher also analyzed the students’ visual representation. The result of hypothesis testing of this research showed that students’ reading comprehension is significantly improved. This strategy developed students’ knowledge on reading sub-skills. Furthermore, the result of the students’ responses toward the strategy was responded positively by the students as it shows the result of 97% at the questionnaire. Therefore, it is suggested to implement visualization metacognitive strategy in improving reading comprehension. In conclusion, this research has demonstrated that the treatment activities have improved the students’ reading comprehension as they enjoy  competition and fun in learning English.